Analysis of Potential Manifestation of Creative Economy for Single Parent (Foster Village-Pudak Sapadu, Kumpeh Ulu District) - Musnaini; Sry Rosita; Fitriaty (Jurnal Ekonomi dan Bisnis Digital, 2022)
This study aims to identify and explain the economic creativity model for Single Parent. The research approach uses the Basic qualitative research approach. The sampling technique used snowball sampling and observation by interviewing 26 key informants who live in the villages of Muara Kumpeh, Pudak, Kasang Pudak, Lopak Alai and Sumber Jaya, namely member villages of PUDAK Sandang Pangan Terpadu (PUDAK SAPADU). The data analysis tool uses ATLAS.ti software (CAQDAS / Computer-Aided Qualitative Data Analysis Software program). The results of the study determine that the integrative hybrid model is a single parent creative economic empowerment pattern. The results of the analysis found that the creative pattern of the single parent economy has three models, namely new businesses, single parent businesses and millennial businesses. The research implications of limited capital, ability, and level of education are taken into consideration by single parents in determining business patterns.